An analysis of Chinese data on root and tuber crop production - Stone, Bruce (Cambridge University Press, 1984)
Soon after the People's Republic of China resumed publishing economic data series in the late 1970s it became clear that current definitional conventions for statistical categories often differed from those of the 1950s. For example, tractor stock, in standard 15 horse-power units from the 1950s, was recorded in series linked with current physical unit data. Sporadic efforts have been made clearly to define categories in different periods, pin down transition dates, and occasionally develop consistent series. In some instances, Chinese statistical organizations have produced series making adjustments for specific inconsistencies in previously published data. Soybeans, for example, are now included in the entire official series for foodgrain production and sown area from 1949 to the present; they were previously excluded from 1949–57 data. Articles by Walker and by Field and Kilpatrick were among attempts to correct for this inconsistency, considerably pre-dating the official published adjustment. At around the same time several researchers noted that roots and tubers were valued at one-fourth natural weight in the 1950s, but one-fifth under current convention. For a few years the transition date was open to question and arguments were tendered in support of 1977, 1970 and 1964. Members of a United States Department of Agriculture delegation to China seem to have ended the debate by simply asking their Chinese hosts. They were told categorically that the official change was in 1964, although it is always possible that the effective date differed somewhat among reporting units or even among provinces. Some four years later the date was confirmed in the 1983 Statistical Yearbook.